Incidence of non-AIDS-defining malignancies in HIV-infected versus noninfected patients in the HAART era: impact of immunosuppression. - Bedimo, Roger J; McGinnis, Kathleen A; Dunlap, Melinda; Rodriguez-Barradas, Maria C; Justice, Amy C (Journal of acquired immune deficiency syndromes (1999), 2009)
The incidence of non-AIDS-defining malignancies (non-ADMs) is reported as unchanged or increasing in the highly active antiretroviral therapy era. Whether incidence of non-ADM is significantly higher in HIV-infected than in HIV-uninfected patients remains unclear.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Case-Control Studies; CD4 Lymphocyte Count; Cohort Studies; HIV Infections; Humans; Incidence; Male; Middle Aged; Neoplasms